Linguistic Politeness Values in Javanese Speech Levels as The Basis of Character Education - Nuryantiningsih, Farida; Hidayat, Ashari (Universitas Negeri Semarang, 2022)
This research aims at exploring the linguistic politeness values in Javanese speech levels. Javanese is a unique language since it has a speech level. It is a linguistic system which regulates how Javanese is used in daily communication. Meanwhile, linguistic politeness is the foundation in improvement of a person’s character to betterment. Politeness values in Javanese speech level teach us in-depth human values. Recently, linguistic politeness started to decline. This also indicates a change in Javanese youths’ politeness values. Therefore, it is very important to study the exploration of linguistic politeness values in Javanese speech level. This article employs a qualitative approach and applies a descriptive method. The data are collected using listening method with tapping technique and listening while speaking advanced technique. In addition, the researcher also employs speaking technique. Data collection with speaking method means conversation between the researcher and informant. The data are analyzed by employing proportionate pragmatic method with hearer as the determinant. This proportionate pragmatic method aims at describing linguistic politeness in interaction using correct Javanese speech level between speaker and hearer in Yogyakarata and Purwokerto.